Financing Long-Term Care: Options for Policy - Walter M. Cadette (Levy Economics Institute of Bard College, 1999)
The nation is ill-prepared to finance the quantum jump in long-term care spending that is on its way as the baby boom ages. By default rather than by design, Medicaid has become the main source of funds for long-term care. But reliance on Medicaid has fostered the institutionalization of the disabled elderly, has given rise to a two-tier care system, and has yielded the bizarre outcome of use of limited welfare funds by middle- and even high-income Americans who have succeeded in sheltering assets from Medicaid's spend-down requirements. Insurance would be a greatly better answer to the nation's long-term care needs. But the market will remain small and underdeveloped as long as Americans can make easy claim on Medicaid. The paper puts forth a plan for universal long-term care insurance, supported by income-scaled tax credits, to replace Medicaid in its current role. That would make for "honest government"–one that not only does not fund inheritance protection but also genuinely protects those with greatest need.
Keywords: 330